“Protein” Industry Convergence and Its Implications for Resilient and Equitable Food Systems - Howard, Philip H.; Ajena, Francesco; Yamaoka, Marina; Clarke, Amber (Frontiers in Sustainable Food Systems, 2021)
Recent years have seen the convergence of industries that focus on higher protein foods, such as meat processing firms expanding into plant-based substitutes and/or cellular meat production, and fisheries firms expanding into aquaculture. A driving force behind these changes is dominant firms seeking to increase their power relative to close competitors, including by extending beyond boundaries that pose constraints to growth. The broad banner of “protein” offers a promising space to achieve this goal, despite its nutritionally reductionist focus on a single macronutrient. Protein firm strategies to increase their dominance are likely to further diminish equity in food systems by exacerbating power asymmetries. In addition, the resilience of food systems has the potential to be weakened as these strategies tend to reduce organizational diversity, as well as the genetic diversity of livestock and crops. To better understand these changes, we visually characterize firms that are most dominant in higher protein food industries globally and their recent strategic moves. We discuss the likelihood for these trends to further jeopardize food system resilience and equity, and we make recommendations for avoiding these impacts.